HUBUNGAN PENGETAHUAN, PENDIDIKAN DAN PELATIHAN DENGAN TINGKAT KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PETUGAS PENYAPU JALAN DI KECAMATAN BANGKINANG KOTA TAHUN 2018 - Rizki Rahmawati Lestari; Adam Pratama Pratama (Universitas Pahlawan, 2019)
Personal protective equipment (PPE) is a device used by workers for their own safety from potential hazards and work accidents that can be done at work. The impact if not using PPE is a work accident. Based on data from the International Labor Organization (ILO) in 2015, workers worldwide die every 15 seconds due to work accidents and 160 workers who are injured as a result of work. The purpose of this study was to study the relationship of knowledge, education and training with the level of use of personal protective equipment (PPE) in Street Sweeper Officers in the District of Bangkinang city in 2018. This type of research is analytic with cross sectional design. The population in this study is the street sweeper in Bangkinang Kota District which accommodates 96 people with a sample of 85 people taken by simple random sampling technique. The results of the study obtained there is a relationship of knowledge with the level of use of PPE with a p value of 0.016, there is a relationship of education with the level of use of PPE with p value0,0,002 and there is a relationship of training with the level of achievement in the use of PPE with a value of p 0,000. It is expected that road sweepers always wear personal protective equipment while working to avoid the risk of workplace accidents.